Reduction of Tannins in Black Tea Using Rice Husk Ash: An Innovation to Reduce The Risk of Iron Deficiency Anemia: Rengganis Wulan Kinasih1, Nadira Mais Fayyaza, Binar Panunggal, Nurmasari Widyastuti, Dewi Marfu'ah Kurniawati - Rengganis Wulan Kinasih; Nadira Mais Fayyazal; Binar Panunggal; Nurmasari Widyastuti; Dewi Marfu'ah Kurniawati (Jurnal Persada Husada Indonesia, 2026)
Research Objective: Depression disorder is a significant mental health issue occurring among adolescents worldwide. Omega-3 fatty acids, vitamin B9, and vitamin B12, influences the body's produced neurotransmitters, especially serotonin, dopamine, and norepinephrine. These neurotransmitters are neurobiological factors contributing to depression disorders. Levels of serotonin, dopamine, and norepinephrine in the body can aid in depression prevention. This research aims to analyze the correlation between the intake of omega-3 fatty acids, vitamin B9, vitamin B12, and depression symptoms in female adolescents at SMAN 9 Semarang. Methodology: This research is observational research with a cross-sectional design, involving 118 female adolescents aged 14 – 18 years. It is selected through non-probability sampling using purposive sampling. Depression symptoms are measured using the BDI-II (Beck’s Depression Inventory) questionnaire, while omega-3 fatty acids, vitamin B9, vitamin B12 are measured using SQ-FFQ (Semi Quantitative Food Frequency Questionnaire). Bivariate data analysis using Chi-Square test and multivariate data analysis using logistic regression. Results: About 30% of female adolescents in X, XI, and XII grades are classified as having moderate depression with a deficiency in omega-3 intake (91.2%), vitamin B9 (88.2%), and vitamin B12 (85.3%). Multivariate analysis showed a relationship between vitamin B9 intake and depressive symptoms in female adolescents (p = <0,001). Conclusion: There is a relationship between vitamin B9 intake and depressive symptoms in female adolescents.